Knowledge of Pregnant Women about Pregnancy Exercise - Dina Indarsita; Sri Siswati; Juliandi Juliandi (Universitas Pahlawan, 2023)
Pregnancy exercise is exercise that is done to prepare and train the muscles so that they can be used to function optimally in normal delivery. Pregnancy exercise is very important for pregnant women. the incidence of prolonged labor in pregnant women who do pregnancy exercise is also smaller than that of pregnant women who do not do pregnancy exercise and in women who do pregnancy exercise their delivery is faster than pregnant women who do not do pregnancy exercise. This is because pregnant women do not know the importance of participating in pregnancy exercise during pregnancy. This type of research is descriptive analytic with a cross sectional study design. Sampling is done by total sampling is a sampling technique when all members of the population are used as samples with a sample of 40 people. The time of the study was April – September 2022. Data were collected from respondents using a questionnaire. Analysis of the data used is univariate (Frequency Distribution). The results showed that there were 24 people (60%) pregnant women who had good knowledge about pregnancy exercise and 16 people (405%) were not good. Conclusion Mothers who have knowledge of pregnant women about pregnancy exercise are more than those who are less good, namely 60% and 40%. Suggestions that health promotion about pregnancy exercise for pregnant women be further improved. With the increased knowledge of mothers about pregnancy exercise, it is hoped that mothers will carry out pregnancy exercise activities so that there will be no occurrence of prolonged labor.